Chapter 5 – Using simple data: surplus production models - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED• How to assess the state of a fishery with a simple series of catch and effort?• How is a fishery model different from a trend analysis?• Do the assumptions of the model affect the management values of interest?• How to word a management advice? Surplus production equilibrium and dynamic models